2021
DOI: 10.1088/1361-6528/ac0b64
|View full text |Cite
|
Sign up to set email alerts
|

Photodiode behaviors of the AgSbS2 nanocrystals in a Schottky structure

Abstract: Cubic phase AgSbS2 nanocrystals (NCs) were synthesized by the hot-injection method, and they were inserted between the Al and p-Si to fabricate Al/AgSbS2/p-Si photodiode by the thermal evaporation method. AgSbS2 NCs were characterized by XRD, SEM and TEM instruments to confirm the crystal phase, surface morphology as well as crystalline size. The XRD pattern revealed that the cubic crystalline structure of the AgSbS2. The spherical shapes and well surface morphology were affirmed by SEM and TEM analysis. Al/Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Schottky-type photodiodes are called metal-semiconductor contacts or heterostructures, and are obtained easily by physical vapor deposition techniques [12,13]. Generally, n-type or p-type Si is used to fabricate Schottky-type photodiodes, and a layer such as metal oxide or polymer sometimes is inserted between the metal and semiconductor to passivate dangling bonds and to control the current conduction mechanism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Schottky-type photodiodes are called metal-semiconductor contacts or heterostructures, and are obtained easily by physical vapor deposition techniques [12,13]. Generally, n-type or p-type Si is used to fabricate Schottky-type photodiodes, and a layer such as metal oxide or polymer sometimes is inserted between the metal and semiconductor to passivate dangling bonds and to control the current conduction mechanism [14].…”
Section: Introductionmentioning
confidence: 99%
“…12 Nanocrystalline detectors based on ternary antimony disulde (including CuSbS 2 and AgSbS 2 ) prepared on a silicon substrate usually exhibit A/W-level responsivity with very high detectivity, attributed to the good photodiode behavior and a high rectifying ratio. 13,14 Nonetheless, the performance is always constrained by the synthesis technology of narrow-bandgap nanocrystals, as well as the stability of nanomaterials. Conjugated polymer infrared PDs have also demonstrated a relatively wide detection range up to 1500 nm, high detectivity exceeding 10 10 Jones, and micrometer-scale response times.…”
Section: Introductionmentioning
confidence: 99%
“…The ternary metal chalcogenides ABX 2 (A = Cu and Ag; B = Sb and Bi; X = S, Se, and Te) have attracted great attention because of their excellent optoelectronic properties, facile processing, superior stability, and great potential for flexible device applications. Among these chalcogenides, AgSbS 2 has been regarded as a potential optoelectronic material due to its suitable bandgap (1.5–1.7 eV), high absorption coefficient (α = 10 5 cm –1 ), and nontoxicity. ,,, Recently, Yang et al reported the high photosensitivity (300 A/W) and excellent detectivity (10 12 Jones) of the phototransistor based on the AgSbS 2 film . However, the reported response time of the as-prepared AgSbS 2 photodetector was on the order of magnitude of seconds, which is far from the requirement (microsecond) in the practical application. , It deserves to reduce the response time of the AgSbS 2 -based photodetectors without degrading other performances.…”
Section: Introductionmentioning
confidence: 99%